THE AUTHENTICATION PROCESS USING GRAPHICAL PASSWORDS - Sergei N. Davydov; Michael Ya. Kleptsov; Larisa V. Lyubimova (Открытое образование (Москва))
In this article the authors review the using of graphical passwords for authentication. The main advantage of this authentication is the users friendly approach. However, with multiple browsing of the logon session, the attacker can see and understand the password. To avoid this drawback, the authors recommend to use dynamic graphical passwords. On three examples of dynamic graphical authentication article demonstrates how with user-friendly, graphical password can be stable.